The pathway to genetic gains in Ethiopian dairy Cattle: Lessons learned from African Dairy Genetic Gains Program and tips to ensure sustainability - Meseret, Selam; Gebreyohanes, Gebregziabher; Mrode, Raphael A.; Ojango, Julie M.K.; Chinyere, Ekine; Hassen, A.; Tera, Asrat; Jufar, B.; Kahumbu, S.; Negussie, E.; Okeyo Mwai, Ally (2022)
In recent years, information and communication technology, and genomic tools have respectively enabled crowd-sourced herd performance recording and fastening of genetic gains in dairy cattle. The African dairy cattle genetic gains (ADGG) program is a collaborative effort of International Livestock Research Institute, Livestock Development Institute, and other national and international partners to foster sustainable genetic improvement. The ADGG program has developed and implemented digital herd performance recording tools, national dairy recording platforms, digital extension services, and genomic evaluation pipelines for Tanzania, Kenya, and Ethiopia. The initial program’s target was to register 12,000 dairy herds in each country, however in Ethiopia’s in 98 districts and 6 regions, more than 74,500 herds and 157,000 animals had been registered by July 2022. The volume and diversity of data being captured by national dairy database is steadily growing. For example, today 440,000 test-day milk yield and 313,000 body weight records have been captured. The above data has been used to undertake the first genomic evaluations, results of which have been publicized in the national Cow and Bull Catalogue for the locally bred but genetically superior bulls and cows. Three of the top ranked bulls have been recruited into the National Artificial Insemination (AI) center for broader use nationally. So far, a total of 67,000 semen straws have been extracted from these bulls and are being used to breed cows and heifers in 14 districts of Ethiopia, thereby not only benefiting many local smallholder dairy farmers, but also significantly saving the country foreign exchange which would otherwise have been used to import bulls and semen from outside the country most of bulls may not be as locally adapted and genetically superior. The great achievement has been realized due to existence of systematic animal identification and consistent performance recording, both of which are crucial for sustained national genetic evaluation, identification, and use of genetically superior and locally adapted dairy breeding stock. Furthermore, identifying roles and responsibilities, and strengthening collaboration among key dairy actors and strong government leadership and support are mandatory to build sustainable breeding program.